Internal corrosion control of water supply systems : code of practice - Hayes, Colin (Metals and related substances in drinking water series. Code of practice series., 2012)
This Code of Practice is concerned with metal pick-up by drinking water within the water supply chain, particularly from water mains and from domestic and institutional pipe-work systems. The principal metals of interest are copper, iron, and lead, and to a lesser extent nickel and zinc. The emphasis is on cold drinking water at its point of use by consumers. Metals arising from water sources and hot water systems are not considered. The intention is that this Code of Practice establishes an international standard for the control of internal corrosion of water supply systems. It provides a basis for identifying both problems and sustainable solutions in a manner which is sound scientifically and will help operators to achieve due diligence. It provides a template for improving internal corrosion control in countries, cities or towns where this has been neglected or poorly implemented. Internal Corrosion Control of Water Supply Systems is deliberately brief in its presentation of a wide array of complex information, in order to provide direction to practitioners that can be more easily related to their specific circumstances. The book also provides a series of check-lists and criteria to be used in risk assessment. EDITOR Dr Colin R Hayes, University of Swansea, UK, Chair of IWA Specialist Group on Metals and Related Substances in Drinking Water. Table of Contents Introduction; Identifying internal corrosion control needs; Selecting appropriate control measures; Implementing a monitoring programme; Risk assessment; On-going management; Key references; 1. Sampling methods and regulatory compliance; Corrosion testing; Compliance modelling; Definition of the term optimisation as it relates to the control of lead in drinking water; Protocols for the optimisation of corrosion control treatment to minimise lead in drinking water; Protocols for the optimisation of corrosion control for copper, iron, nickel and zinc in drinking water; Design of pipework systems in buildings; Partial lead service line replacement with copper pipe and galvanic corrosion; Internal corrosion control in small supplies; Check-lists and criteria for risk assessment.